Unlocking the Potential of Input-Output Tables for Spatial Analysis Using the Miyazawa Model: A Case Study of East Java Province - Murjani, Ahmadi; Wiratama, Budhi Fatanza (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
East Java Province holds a strategic role in the national economy, serving as the second-largest contributor to GDP after Jakarta and as a key trade hub to Eastern Indonesia. Yet regional disparities remain substantial, particularly reflected in the economic underdevelopment and weak logistics connectivity of Madura Island, which lies adjacent to the Gerbangkertosusila growth corridor. Addressing this gap requires a deeper understanding of sectoral and spatial linkages that shape Madura’s growth trajectory. This study applies the Miyazawa Input-Output Model for East Java Province, integrating 17 economic sectors and 38 regencies/municipalities to enable simultaneous sectoral and regional analysis. The simulations assess the effects of increasing household income in Madura, spillover from surrounding regions, and the combined role of strengthening the Transportation and Warehousing sector alongside Agriculture and Manufacturing. The findings show that the logistics sector in Madura, when considered independently, has limited impact; however, its significance rises when complemented by productive local sectors. Moreover, spillover from surrounding regions into Madura proves weaker than spillover directed outside Madura, underscoring the island’s fragile spatial connectivity. These results highlight the urgency of affirmative policies that strengthen productive sectors, enhance interregional linkages, and ensure Madura’s integration into East Java’s broader economic development.